1991
DOI: 10.1113/jphysiol.1991.sp018708
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of cardiac troponin C into rabbit muscle does not alter the length dependence of Ca2+ sensitivity of tension.

Abstract: SUMMARY1. The isometric length-tension relationship for cardiac muscle is generally steeper than for skeletal muscle in the physiological range of sarcomere lengths. Recent studies suggest that cardiac troponin C (cTnC) may have intrinsic properties that confer greater length-dependent changes in Ca2+ sensitivity of tension than for skeletal troponin C (sTnC). We tested this hypothesis by characterizing tension-pCa (pCa is -log [Ca2+]) relationships in rabbit skinned psoas muscle fibres at mean sarcomere lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 50 publications
(82 reference statements)
6
42
2
Order By: Relevance
“…Numerous studies have demonstrated that the Ca 2ϩ sensitivity of both cardiac and skeletal myocyte preparations can be altered by replacing endogenous cTnC or skeletal TnC with other TnC isoforms or mutants (17,19,25,27,28). However, this is the first known study in which the Ca 2ϩ sensitivity of force generation in cardiac myocytes has been substantively increased by replacing endogenous cTnC with a mutant McTnC isoform.…”
Section: Camentioning
confidence: 78%
“…Numerous studies have demonstrated that the Ca 2ϩ sensitivity of both cardiac and skeletal myocyte preparations can be altered by replacing endogenous cTnC or skeletal TnC with other TnC isoforms or mutants (17,19,25,27,28). However, this is the first known study in which the Ca 2ϩ sensitivity of force generation in cardiac myocytes has been substantively increased by replacing endogenous cTnC with a mutant McTnC isoform.…”
Section: Camentioning
confidence: 78%
“…This hypothesis is based on molecular differences between TnC of cardiac and skeletal muscle, which might be associated with the difference in the force-length relationship in both muscles. However, several studies have refuted this hypothesis 23,24 . In one of them, Moss et al 23 characterized the relation between force produced and activation induced by Ca 2+ , at sarcomere lengths of 2.32 µm and 1.87 µm in membrane-free rabbit skeletal muscle fibers.…”
Section: The Degree Of Activation Of Cardiac Muscle Depends On Musclementioning
confidence: 95%
“…However, several studies have refuted this hypothesis 23,24 . In one of them, Moss et al 23 characterized the relation between force produced and activation induced by Ca 2+ , at sarcomere lengths of 2.32 µm and 1.87 µm in membrane-free rabbit skeletal muscle fibers. Measurements were performed prior to and following substitution of TnC by cardiac muscle TnC to determine whether this was the main reason for the differences in force-length relationships of skeletal and cardiac muscle.…”
Section: The Degree Of Activation Of Cardiac Muscle Depends On Musclementioning
confidence: 95%
“…This asymmetry in the force-Ca 2ϩ relationship was quantified by regression analysis of the linearized form of the Hill relationship (Eq. 2) (28,33,34). The average Hill parameters that were obtained via this analysis are summarized in Table 2 (parameters n 1 and n 2 ).…”
Section: Ca 2ϩmentioning
confidence: 99%
“…To assess the asymmetry in the force-Ca 2ϩ relationship, linear regression analysis was performed using a modified, linearized form of the Hill equation (28,33,34) Log ͓F fr /͑1 Ϫ F fr ͔͒ ϭ n ⅐ ͕log ͓͑Ca 2ϩ ͔͒ Ϫ log ͑EC 50 ͖͒ (2) in which Ffr represents force development as a fraction of Fmax. The slope of this relationship is governed by the Hill coefficient (n), while the zero crossing represents the EC50 parameter.…”
Section: Preparation Of Right Ventricular Cardiac Trabeculaementioning
confidence: 99%